The tao of travel enlightenments from lives on the road - Theroux, Paul
A collection of writings from Paul Theroux's fifty years of travel. Included are writings from other travelers such as Charles Dickens, Eudora Welty, Anton Chekhov, Ernest Hemingway and many others.